2013
DOI: 10.1179/1973947813y.0000000092
|View full text |Cite
|
Sign up to set email alerts
|

miR-381, a novel intrinsic WEE1 inhibitor, sensitizes renal cancer cells to 5-FU by up-regulation of Cdc2 activities in 786-O

Abstract: miR-381 increases sensitivity of 786-O cells to 5-FU by inhibitory WEE1 and increase of Cdc2 activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 34 publications
0
37
0
1
Order By: Relevance
“…In line with our findings, Huang et al (2017) reported that miR-381 could enhance DDP sensitivity of non-small cell lung cancer cells through nuclear factor-ĸB signaling inhibition. Moreover, several other studies have reported that lowed miR-381 expression was implicated with chemoresistance of other drugs in cancers (Chen et al, 2013;Xu Figure 5 miR-381 promoted DDP sensitivity of breast cancer cells by directly suppressing MDR1 expression. MCF-7/DDP and MDA-MB-231/ DDP cells were transfected with miR-con, miR-381, miR-381þVector, or miR-381þMDR1; and MCF-7 and MDA-MB-231 cells were transfected with anti-miR-con, anti-miR-381, anti-miR-381þsi-con, or anti-miR-381þsi-MDR1, followed by determination of MDR1 expression by qRT-PCR analysis (A and B), IC50 of DDP by MTT assay (C and D), and cell apoptotic rate by flow cytometry analysis (E and F).…”
Section: Discussionmentioning
confidence: 97%
“…In line with our findings, Huang et al (2017) reported that miR-381 could enhance DDP sensitivity of non-small cell lung cancer cells through nuclear factor-ĸB signaling inhibition. Moreover, several other studies have reported that lowed miR-381 expression was implicated with chemoresistance of other drugs in cancers (Chen et al, 2013;Xu Figure 5 miR-381 promoted DDP sensitivity of breast cancer cells by directly suppressing MDR1 expression. MCF-7/DDP and MDA-MB-231/ DDP cells were transfected with miR-con, miR-381, miR-381þVector, or miR-381þMDR1; and MCF-7 and MDA-MB-231 cells were transfected with anti-miR-con, anti-miR-381, anti-miR-381þsi-con, or anti-miR-381þsi-MDR1, followed by determination of MDR1 expression by qRT-PCR analysis (A and B), IC50 of DDP by MTT assay (C and D), and cell apoptotic rate by flow cytometry analysis (E and F).…”
Section: Discussionmentioning
confidence: 97%
“…For tumor growth, miR-381 could inhibit cell proliferation in colon cancer through targeting LRH-1 (17), in glioma through targeting BRD7 (17) and in renal cancer through targeting WEE1 (18). MiR-381 also could sensitize glioblastoma cells to temozolomide by targeting neurofilament light polypeptide (19).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, increased serum levels of miR-183 correlate with patients' resistance to NK cytotoxicity [278] while miR-942 confers resistance of RCC patients to sunitinib [279]. It was also shown that miR-381 enhances the sensitivity of RCC cells to 5-fluorouracil [280].…”
Section: Renal Cancermentioning
confidence: 99%